Developing the School Safety Perception Scale: The Validity and Reliability of Study - Mustafa Kemal ERÇEK; Fırat KIYAS BİREL (Dinamika Ilmu, 2021)
The purpose of this research is to develop a scale to determine the perceptions of teachers working in secondary schools related to school safety. Alongside the social actors, the elements involved in achieving the goals of educational activities are important actors in the solution and implementation of the school security problems. Therefore, the actors performed in this way and were want teachers' perception of safety education activities in schools is critical. The research includes a scale development study.   Certain steps in the scale of development for secondary teacher’s perceptions of school safety were monitored. Reliability and Validity Scale with work related to the development of exploratory and confirmatory factor analyzes were performed. Exploratory factor analysis of the obtained 40-item scale 54.233 discloses % of the total variance. Analyzes showed that reliability coefficients of scale factors ranged from .769 to .893. These values are enough to pass to the confirmatory factor analysis. Confirmatory factor analysis results showed that SSS is a valid tool to measure teachers’ perceptions about school safety. Structures of this study, data collected through school safety scale set Cronbach's alpha was calculated in order to determine the internal consistency. Application in terms of behavior and School Safety "Although low compared to other dimensions of size with .61, scale and reliability coefficients ranged between .80 and .93 for the dimensions have been determined to be highly reliable. İmplications for Research and Practice: With the help of the developed scale, relations between school safety perceptions and personal variables, organizational stress, school climate, use of security technologies, occupational burnout and organizational commitment can be examined. Effects of student perceptions of school safety on their academic success can be researched. Similar scales can be developed for parents, administrators, preschool, elementary school teachers, lecturers, and university students.